Prevalence and Factors Related to Functional Status of Older Adult Patients in Primary Health Care - Eriska, Winda; Wati, Dwi Nurviyandari Kusuma; Rachmawati, Utami; Rekawati, Etty (JURNAL CITRA KEPERAWATAN, 2023)
Functional status means the ability to perform self-care, self-maintenance, and daily activity. Older adults are at risk of experiencing a decline in functional status regarding their condition and other factors. The study literature found no clear evidence of the factors related functional status of older adults, especially those who have comorbid and regularly come to the geriatric clinic in the Primary Health Care Center. This study aimed to identify the prevalence and factors related to the functional status of older people who visit geriatric out-patient in the primary health care center. A cross-sectional design was utilized to assess 100 samples of older adult patients in one Primary Health Care Center, in Indonesia. The functional status of the respondent was good where the mean score was 7.45 (SD = 1.07) with a minimum score was 2, and a maximum score was 8. The mean age of the sample was 66 years old, the gender was primarily women (59%), the education level of the respondents was more likely only reach elementary school (45%), and primarily they consume drugs (71%) and also more than a half of respondent have multimorbidity (60%). The model fit of multivariate analysis resulted in 44% of all the variables giving effect to the functional status where the most influential factor was balance and health status of the older adults. Discussion: More than half of the older people who regularly visit the Primary Health Care Center have an excellent functional status. This condition is in accordance with the experience of older people itself who most of them could come to the clinic independently by public or private transportation. Older people who have good health or balance status and less morbidity also show a good performance in functional status, though, their age was older. All the variables give 44% effects of older people’s functional status where the most influential factor for functional status of the older adults was balance status. Therefore, the accessibility of health services for the older adult in the community can be improved by providing more elderly-friendly health facilities.